Morphological and molecular differentiation of Staphylocystis clydesengeri n. sp. (Cestoda, Hymenolepididae) from the vagrant shrew, Sorex vagrans (Soricomorpha, Soricidae), in North America - Tkach, Vasyl V.; Makarikov, Arseny A.; Kinsella, John M. (Zootaxa, 2013)
Staphylocystis clydesengeri n. sp. is described from shrews Sorex vagrans in Montana and Washington, United States. It differs from the only previously known North American representative of the genus, S. schilleri, in having more numerous (37–42 vs 22–30) and larger (39–44 µm vs 27–30 µm) rostellar hooks. The two species also differ in several other important characters such as relative length of the cirrus pouch, position of gonads and shape of mature proglottides. Morphological differentiation of the new species from all previously known Palearctic species of Staphylocystis from Sorex is also provided. Differentiation from Staphylocystis parasitic in crocidurine shrews is not provided due to the high level of specificity among shrew hymenolepidids to the host genera and much greater levels of sequence divergence between Staphylocystis from the two groups of shrews. Molecular differentiation based on 2,800 base pair long sequences of nuclear ribosomal RNA (complete ITS region and partial 28S region), 663 base pair long sequences of mitochondrial nad1 gene and 542 base pair long sequences of mitochondrial ribosomal 16S gene strongly support the status of Staphylocystis clydesengeri n. sp. Relative utility of the DNA fragments used in this study for reliable differentiation among closely related species of mammalian hymenolepidids is discussed. Nuclear ribosomal RNA region appears to be too conserved for this purpose. Use of at least one mitochondrial gene in addition to nuclear ribosomal RNA or without it, is recommended. Vampirolepis novosibirskiensis Sawada & Kobayashi, 1994 is transferred to Staphylocystis as a junior synonym of S. furcata (Stieda, 1862). Rodentolepis gnoskei Greiman & Tkach, 2012 is transferred to Pararodentolepis Makarikov and Gulyaev, 2009 as a new combination Pararodentolepis gnoskei (Greiman & Tkach, 2012) n. comb.